Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Artdeco Inti Kreasi Jakarta Timur - Azkiya, Nada Isna; Pramularso, Eigis Yani; Hardani, Hardani (MARGIN ECO, 2025)
Companies must continue to pay attention to the role of their human resources. The attention that can be paid by the company can be in the form of discipline and compensation provided so that the performance of its employees is also maintained. This study aims to determine the influence of compensation and work discipline on employee performance at PT Artdeco Inti Kreasi. The analysis method of this study uses quantitative data collection techniques in the form of questionnaires or questionnaires. The sample in this study is 40 respondents who are all employees at PT Artdeco Inti Kreasi. The data analysis used was validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, linearity test, multiple linear regression analysis with SPSS 26 data processing. The results of this study state that compensation has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Compensation and discipline simultaneously affect employee performance